Cold tolerance of native plants in the Lancang River dry–hot valley: an integrative physiological–biochemical assessment with implications for cold-resistance breeding - Zhang, Yunchen; Yang, Jianying; Yuan, Xu; Yang, Yandong; Ji, Xiaodong; Ji, Jinnan; Zhang, Yan; Huang, Jiao (Frontiers in Plant Science, 2026)
IntroductionExtreme winter cold in the Lancang River dry–hot valley limits vegetation establishment. Selecting cold-tolerant native species is therefore critical for ecological restoration and for maintaining stable agro-vegetation. This study aimed to assess cold tolerance in representative native shrubs and herbs using an integrated physiological and biochemical approach.MethodsSeedlings of three shrubs (Sophora davidii, Vitex negundo var. microphylla, Rumex hastatus) and two herbs (Arthraxon lanceolatus, Artemisia vestita) were exposed to temperatures from 25°C down to –35°C in growth chambers. We quantified membrane injury (relative electrolyte leakage and semilethal temperature, LT50), gas exchange, chlorophyll fluorescence, osmolyte levels (proline, soluble sugars), and antioxidant enzyme activities (e.g., superoxide dismutase). Multivariate analyses (principal component analysis and membership functions) were used to develop an integrated cold-tolerance index.ResultsSemilethal temperature (LT50) differed markedly among species (approximately –27°C in S. davidii vs –5°C in A. lanceolatus), indicating a wide range of freezing tolerance. Across the freezing gradient, S. davidii maintained the lowest electrolyte leakage and partial Photosystem II efficiency, while accumulating high proline and soluble sugar levels and sharply increasing superoxide dismutase activity. In contrast, A. lanceolatus showed rapid membrane leakage and fluorescence declines. The most informative cold-response traits were Photosystem II efficiency and electrolyte leakage. An integrated cold-tolerance index based on multiple physiological metrics ranked species from highest to lowest tolerance as A. vestita > A. lanceolatus > V. negundo > R. hastatus > S. davidii. This ranking differed notably from the ranking based on LT50 alone.DiscussionThe discrepancy between the multi-trait index and single-trait (LT50) ranking highlights the risk of inferring cold tolerance from one metric. Acute stress responses (membrane stability, photosynthesis) and long-term freezing thresholds capture complementary aspects of cold tolerance. The derived physiological thresholds and the multi-indicator framework provide practical guidance for selecting and breeding native species for ecological restoration and cold-resilient agriculture in dry–hot valleys.